Clinicopathological, Radiological, and Molecular Features of Primary Lung Adenocarcinoma with Morule-Like Components. (12th June 2021) - Wang, Li-Li; Ding, Li; Zhao, Peng; Guan, Jing-Jing; Ji, Xiao-Bin; Zhou, Xiao-Li; Shao, Shi-Hong; Zou, Yu-Wei; Fu, Wei-Wei; Lin, Dong-Liang
Abstract : Background . Morule-like component (MLC) was a rare structure in primary lung adenocarcinoma. We aimed to reveal the clinicopathological, radiological, immunohistochemical, and molecular features of lung adenocarcinoma with MLCs. Methods . Twenty lung adenocarcinomas with MLCs were collected, and computed tomographic and histological documents were reviewed. Immunohistochemistry, targeted next-generation sequencing, and Sanger sequencing for β-catenin gene were performed. Results . There were 9 lepidic adenocarcinomas, 8 acinar adenocarcinomas, 2 papillary adenocarcinomas, and 1 minimally invasive adenocarcinoma. Most patients (16/17) were shown a pure solid nodule, and 1 patient was shown a partly solid nodule on chest computed tomography (CT). Nine cases were accompanied with micropapillary components, and 3 were with cribriform components in which 2 suffered a worse prognosis. No significant association was found between the MCLs and the overall survival of lung adenocarcinoma (P = 0.109 ). The MLCs were often arranged in whorled or streaming patterns. The cells in MLCs showed syncytial and mild appearance. The MLCs were positive for E-cadherin, CK7, TTF-1, napsin-A, vimentin, and β -catenin (membrane), and negative for CK5/6, p40, p63, Synaptophysin, chromogranin A, and Cdx-2. EGFR mutation, ALK-EML4 fusion, HER 2 amplification, and PIK3CA mutation were detected in 16 cases, 2 cases, 1 case, and 1 case, respectively. EGFR mutation was more frequent in adenocarcinomas with MLCs than those without MLCs (P = 0.040 ). β-catenin gene mutation was not detected in any patients. Conclusions . MLC is often observed in the background of acinar, lepidic, and papillary adenocarcinomas. Lung adenocarcinomas with MLCs tend to appear as a solid mass on CT and harbor EGFR gene mutations. The micropapillary components and cribriform components may cause poor prognosis of lung adenocarcinomas with MLCs. Vimentin is always positive in MLCs, and it is a useful marker for the identification of MLCs.